2020
DOI: 10.1190/geo2019-0238.1
|View full text |Cite
|
Sign up to set email alerts
|

Improved well-log classification using semisupervised label propagation and self-training, with comparisons to popular supervised algorithms

Abstract: Machine-learning techniques allow geoscientists to extract meaningful information from data in an automated fashion, and they are also an efficient alternative to traditional manual interpretation methods. Many geophysical problems have an abundance of unlabeled data and a paucity of labeled data, and the lithology classification of wireline data reflects this situation. Training supervised algorithms on small labeled data sets can lead to overtraining, and subsequent predictions for the numerous unlabeled dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, semi-supervised or unsupervised learning is required to relieve the dependence on labels. Dunham et al (2019) focused on the application of semi-supervised learning in a situation in which the available labels were scarce. A self-training-based label propagation method was proposed, and it outperformed supervised learning methods in which unlabeled samples were neglected.…”
Section: Semi-supervised and Unsupervised Learningmentioning
confidence: 99%
“…Therefore, semi-supervised or unsupervised learning is required to relieve the dependence on labels. Dunham et al (2019) focused on the application of semi-supervised learning in a situation in which the available labels were scarce. A self-training-based label propagation method was proposed, and it outperformed supervised learning methods in which unlabeled samples were neglected.…”
Section: Semi-supervised and Unsupervised Learningmentioning
confidence: 99%
“…Participants used various models, including k-nearest neighbors, neural networks, support vector machines, and boosted tree models (Hall and Hall, 2017), with the most accurate model utilizing a boosted tree approach with a median accuracy of 0.64 from nine classes (Hall and Hall, 2017). The dataset provided in the contest is still being used today for new ML-based facies prediction studies (e.g., Dunham et al, 2020). This contest demonstrated that well log data is a powerful data type for ML-based lithology and facies prediction, but logs are low-resolution data, typically only resolving vertically ∼0.3 m for gamma ray, ∼0.5 m for density, and ∼0.1 m for photoelectric tools (Rider and Kennedy, 2011).…”
Section: Introductionmentioning
confidence: 99%